ARCHITECTURE CONSIDERATIONS FOR COMMUNITIES OF SMART OBJECTS (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
The article presents the origin of the Internet of Things (IoT) and how the concept has evolved over time. Four architectures for IoT implementations are identified and described: central point architecture, decentralized architecture, hybrid architecture, and semi-centralized architecture. Next, the concept of an intelligent object is defined, and its characteristic aspects are described. Finally, an example of implementation is given, and conclusions are drawn.
Keywords: Internet of Things; Architectures; Smart objects; Edge computing; Fog computing; Mist computing; Mesh network; Microservices; Raspberry Pi